2018
DOI: 10.18632/oncotarget.25531
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming drug-tolerant cancer cell subpopulations showing AXL activation and epithelial-mesenchymal transition is critical in conquering ALK-positive lung cancer

Abstract: Anaplastic lymphoma kinase tyrosine kinase inhibitors (ALK-TKIs) induce a dramatic response in non–small cell lung cancer (NSCLC) patients with the ALK fusion gene. However, acquired resistance to ALK-TKIs remains an inevitable problem. In this study, we aimed to discover novel therapeutic targets to conquer ALK-positive lung cancer. We established three types of ALK-TKI (crizotinib, alectinib and ceritinib)-resistant H2228 NSCLC cell lines by high exposure and stepwise methods. We found these cells showed a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 52 publications
1
30
0
Order By: Relevance
“…Such HSP90-inhibiting treatments resulted in depletion of the CSC fractions (CD44/ALDH double-positive cells) and downregulation of specific microRNAs associated with CSCs' resistance to chemotherapy [72]. Taken together, all these publications [65][66][67][68][69][70][71][72] testify the important role of HSP90 in forming the CSC phenotype through EMT, although there may be multiple HSP90-mediated mechanisms of triggering and promoting EMT in different types of cancer.…”
Section: Intracellular Hsp90 and Some Of Its Partners In Chaperoningmentioning
confidence: 91%
See 2 more Smart Citations
“…Such HSP90-inhibiting treatments resulted in depletion of the CSC fractions (CD44/ALDH double-positive cells) and downregulation of specific microRNAs associated with CSCs' resistance to chemotherapy [72]. Taken together, all these publications [65][66][67][68][69][70][71][72] testify the important role of HSP90 in forming the CSC phenotype through EMT, although there may be multiple HSP90-mediated mechanisms of triggering and promoting EMT in different types of cancer.…”
Section: Intracellular Hsp90 and Some Of Its Partners In Chaperoningmentioning
confidence: 91%
“…Using selective inhibitors of the HSP90 chaperone activity or techniques with HSP90 knockdown, it was shown that intracellular HSP90 can be conducive to EMT in carcinomas of different localization [65][66][67][68][69][70][71], while the mechanisms of such HSP90-dependent EMT may vary in different cases. So, intracellular HSP90 was reported to promote EMT via (i) activation of HIF1α and NFκB [65] and stabilization of an oncogenic nonhistone chromatin-binding protein high-mobility group AT-hook 2 (HMGA2) [66] in colorectal cancer cells, (ii) activation of the TGF-β1/Notch1 signaling [67] or anaplastic lymphoma kinase (ALK) signaling [68] in different variants of lung cancer, (iii) direct interactions with Twist1 to stabilize and activate the latter in hepatocellular carcinoma [69], (iv) stabilization of low-density lipoprotein receptor-related protein 5 (LRP5) followed by LRP5-mediated stimulation of Wnt/beta-catenin signaling in gastric cancer [70], and (v) activation of STAT3 followed by the Twist1 expression upregulation in ovarian, renal, and nasopharyngeal cancer [71].…”
Section: Intracellular Hsp90 and Some Of Its Partners In Chaperoningmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, ALK-EML4 translocation in NSCLC is associated to EMT and induces a CSC phenotype [ 132 ]. Several studies have also shown that EMT was associated with resistance to crizotinib (a first generation TKI targeting ALK and ROS1), through tumor hypoxia [ 133 ], activation of another tyrosine kinase receptor (AXL) [ 134 , 135 , 136 ] or TGF-β pathway [ 134 ]. In a cell line with ROS1 translocation, resistance to crizotinib was mediated by EMT and Twist1 activation [ 137 ].…”
Section: Shh Pathway and Resistance To Tyrosine Kinase Inhibitorsmentioning
confidence: 99%
“…Additionally, ALK inhibition changes the cell phenotype to an epithelial one [ 209 ]. In a recent paper by Nakamichi et al [ 210 ], H2228 lines resistant to three different ALK inhibitors (crizotinib, alectinib, and ceritinib) were created. The obtained stable line was characterized by a reduced ALK expression and overexpression of another oncogenic protein, AXL, which is associated with EMT and stem cells.…”
Section: Emt and Resistance To Antitumor Therapy: Role In The Formatimentioning
confidence: 99%